The role of biofilm matrix composition in controlling colony expansion and morphology. Issue 6 (14th October 2022) - Charlton, Samuel G. V.; Kurz, Dorothee L.; Geisel, Steffen; Jimenez-Martinez, Joaquin; Secchi, Eleonora
Abstract : Biofilms are biological viscoelastic gels composed of bacterial cells embedded in a self-secreted polymeric extracellular matrix (ECM). In environmental settings, such as in the rhizosphere and phyllosphere, biofilm colonization occurs at the solid–air interface. The biofilms' ability to colonize and expand over these surfaces depends on the formation of osmotic gradients and ECM viscoelastic properties. In this work, we study the influence of biofilm ECM components on its viscoelasticity and expansion, using the model organism Bacillus subtilis and deletion mutants of its three major ECM components, TasA, EPS and BslA. Using a multi-scale approach, we quantified macro-scale viscoelasticity and expansion dynamics. Furthermore, we used a microsphere assay to visualize the micro-scale expansion patterns. We find that the viscoelastic phase angle Φ is likely the best viscoelastic parameter correlating to biofilm expansion dynamics. Moreover, we quantify the sensitivity of the biofilm to changes in substrate water potential as a function of ECM composition. Finally, we find that the deletion of ECM components significantly increases the coherence of micro-scale colony expansion patterns. These results demonstrate the influence of ECM viscoelasticity and substrate water potential on the expansion of biofilm colonies on wet surfaces at the air–solid interface, commonly found in natural environments.